DESIGN, SIMULATION, AND EXPERIMENT OF FLOATING PHOTOVOLTAIC WITH THERMOSIPHON CASCADE COOLING SYSTEM - Azka, Muhammad
Global warming and climate change have increased the use of renewable energy, one of which is solar energy, where photovoltaic (PV) is currently growing rapidly with increasingly cheap prices and high efficiency, but there are still constraints on land requirements. Floating PV is one of the solution, especially because Indonesia has many lakes and high intensity of sunlight. In this research, a passive thermosiphon cascade cooling technology was developed which is suitable for floating solar power plants to increase power & efficiency, where this research is a development from the thermosiphon cooling research by Sutanto (2018). In principle, the cooling fluid absorbs the heat from PV and is cooled again by passing the cooling channel back into the water so that it can recool the next PV, where the cooling fluid circulation occurs continuously due to the bouyancy effect. In the beginning, Computational Fluid Dynamics simulation for thermosiphon cascade system configuration was carried out, showing that the circuliaton of cooling fluid is happened, which is indicated by a temperature gradual change in the cooling fluid. The test was carried out as a validation of the simulation by comparing the temperature and power parameter in four different configurations, namely ground PV, floating PV, floating PV with conventional thermosiphon, and floating PV with thermosiphon cascade. The test results show that the working temperature of PV that cooled by thermosiphon cascade system is 4°C lower than the conventional thermosiphon, because the cooling fluid between PV can be cooled back to 14.5°C due to the cascade system. This gives impact in increasing of power & efficiency of floating PV with thermosiphon cascade by 8.48% & 8.67% compared to ground PV, higher than the floating PV with conventional thermosiphon compared to ground PV (7.09% and 7.18%) and floating PV compared to ground PV (4.96% and 4.93%).